Investor panic, IMF actions, and emerging stock market returns and volatility: A panel investigation - Bernd Hayo; Ali M. Kutan (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
In this paper, we examine the reaction of stock market returns and volatility in a diverse group of six emerging markets to a set of IMF events. In particular, we test within a panel framework whether there was an “investor panic” causing a significant drop in stock market returns on the days of negative IMF events. We find that on average negative (positive) IMF news reduce (increase) daily stock returns by about one percentage point. The most influential single event is the delay of loans from the IMF, which reduces stock returns by about one and a half percentage points. IMF news do not have a significant impact on the volatility of stock markets. Thus, it appears that IMF actions and events primarily have an effect on pay-offs but not on risk, and do not appear to support the hypothesis of IMF induced “investor panics”.
Keywords: F300; G100; 330; IMF news; stock market returns; emerging markets